EFFECTIVENESS OF ENGLISH LEARNING BASED ON ONLINE / E-LEARNING IN STUDENT'S VIEW OF THE UNIVERSITY OF LABUHANBATU - Nova Jayanti Harahap (Jurnal Education and Development, 2022)
This study aims to determine the effectiveness of E-Learning-based English learning. E-learning is an educational system or concept that utilizes information technology in the teaching and learning process. This study uses a qualitative description of research and data analysis. Data was collected using the participant interview method directly by the lecturer to class A students of Labuhanbatu University 2 semester, as many as 38 people. The results of this study can be seen directly how the effectiveness of E-Learning-based in learning English. In fact, the results obtained from the study showed that 18 respondents stated that online learning was less effective, 14 respondents stated that learning was effective, and 6 respondents stated that it was very ineffective. Most students feel that online learning is less effective due to several reasons such as poor network, traffic jams, network errors, when asking students to ask lecturers is less effective. Utilization of E-learning by using teaching strategies, using videos and social media applications such as Instagram and Facebook is considered to be able to foster student interest in learning English.